Implementasi Pendekatan Multiple Intelligence dalam Pembelajaran Anak Usia Dini di Playgroup & Kindergarten Ananda Mentari Yogyakarta - Siti Kamilah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2019)
This research is to describe the Implementation of Multiple Intelligences Approach in Early Childhood Learning, which consists of: learning planning, learning implementation, and evaluation of classroom learning in Playgroup and Kindergarten Ananda Mentari Condongcatur, Yogyakarta. This research uses descriptive method with a qualitative approach. The subjects of this study were 1 principal, 2 kindergarten teachers, 1 education staff, 1 toddler teachers. The object of research is the application of Multiple Intelligences in Early Childhood learning. Data collection techniques were carried out using structured interviews, observations, documentation and field notes. The research instrument uses an interactive model that includes data reduction, data presentation and drawing conclusions. The validity of the research data was tested using triangulation techniques and source triangulation. The results of the study show that: (1) Planning of learning programs using the Multiple Intelligences approach uses a curriculum adapted from 4 countries, (2) The implementation of learning activities through the Multiple Intelligences approach is integrated into learning materials compiled in the curriculum break down (curriculum outline) in every week, methods and materials for students use English. (3) Evaluation of learning is carried out using checklists and anecdotes according to the age of child development and the development of multiple intelligences approaches is done by playing roles, singing, telling stories, field trips, involving children directly in making projects, discussions, outbound, Student-Led Conference and so on. Learning that involves all the intelligence of students will have a positive impact on the child's future, and increase children's confidence, so he can say